Analysis Behavior of the Millennial Muslim Generation in Paying Zakat Digitally: English - Nur Kholis; Ghozali, Imam; Harto, Puji (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2025)
This study aims to test the perception of ease, level of trust, and brand awareness moderated by the level of religiosity towards the decision of the millennial Muslim generation muzaki in paying zakat digitally. This study uses a quantitative approach method with research respondents who are the millennial Muslim generation in Solo Raya (Surakarta, Klaten, Boyolali, Karanganyar, Wonogiri, Sragen). The analytical tool used in this study is SEM-PLS (Structural Equation Modeling-Partial Least Square) Analysis using SmartPLS version 4.0. based on the results of the analysis, it shows that the perception of ease and brand awareness have a significant effect on the decision of the millennial Muslim generation muzaki in paying zakat digitally, while the level of trust does not have a significant effect on the decision of the millennial Muslim generation muzaki in paying zakat digitally. The level of religiosity is unable to moderate the relationship between the perception of ease, level of trust and brand awareness towards the decision of the millennial Muslim generation muzaki in paying zakat digitally